2008
DOI: 10.1002/pat.1107
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured polyolefins/clay composites: role of the molecular interaction at the interface

Abstract: The extent of interphase interactions between polymer phase and inorganic particles is the driving force addressing the preparation/properties design in the field of the corresponding micro‐ and nanocomposites. In the case of preparation of nanocomposites based on polyolefins (POs) and inorganic compounds as potentially nanodispersed phase, the use of a PO with proper functional groups is necessary for the interface adhesion and stabilization of the nanostructured morphology. According to this approach, ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…This conclusion agrees with FTIR analysis, that suggests that the simultaneous mixing of the clay, polymer, peroxide and functionalizing agent (Method I) is less effective in regard to the modification of PP. Passaglia et al ., while analyzing a propylene copolymer with low ethylene content, also found that the application of mixing methods equivalent to our Methods II and III produce a reduction of the molecular weight of the polymer (as revealed by the drop in the final torque during mixing). They also found that sequential mixing (equivalent to Method III) produces a larger reduction in molecular weight and a better dispersion of the clay particles.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…This conclusion agrees with FTIR analysis, that suggests that the simultaneous mixing of the clay, polymer, peroxide and functionalizing agent (Method I) is less effective in regard to the modification of PP. Passaglia et al ., while analyzing a propylene copolymer with low ethylene content, also found that the application of mixing methods equivalent to our Methods II and III produce a reduction of the molecular weight of the polymer (as revealed by the drop in the final torque during mixing). They also found that sequential mixing (equivalent to Method III) produces a larger reduction in molecular weight and a better dispersion of the clay particles.…”
Section: Resultssupporting
confidence: 55%
“…Although the use of low concentrations of a compatibilizer is the most used scheme among melt mixing methods, various other strategies of compatibilization between inorganic loadings and PP have been reported. For example, pretreatment of the loading with coupling agents; generation of radicals which react with both, the PP free radicals generated during processing and with the loading via , for example, electron transferring; incorporation of monomers which undergo grafting onto PP during processing using a peroxide to initiate the grafting, etc. In particular, the in situ functionalization of PP during blending with o‐MMT is an interesting alternative among melt mixing methods because it is easily implemented in current industrial processes and may promote clay exfoliation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, two different synthetic approaches were very recently compared for the preparation of EPM and PP OLS nanocomposites [89] (Figure 13.9 ):…”
Section: The One -Step Processmentioning
confidence: 99%
“…Literature data further indicate that the number of grafted functional groups as well as the molecular weight and polymer architecture affect the degree of intercalation/exfoliation . Similarly, effective interactions between functionalized POs and clay lamellae are evidenced by blending a diethyl maleate (DEM) functionalized EPM with increasing amounts of an organo‐layered silicate . Interestingly, it has been found that the grafted ester groups interact via hydrogen bonds with the OH groups present on the surface of the clay.…”
Section: Introductionmentioning
confidence: 98%